β-cell Failure as a Complication of Diabetes - Chang-Chen, KJ (Rev Endocr Metab Disord, 2008)
Type 2 diabetes mellitus is a complex disease characterized by β-cell failure in the setting of insulin resistance. In early stages of the disease, pancreatic β-cells adapt to insulin resistance by increasing mass and function. As nutrient excess persists, hyperglycemia and elevated free fatty acids negatively impact β-cell function. This happens by numerous mechanisms, including the generation of reactive oxygen species, alterations in metabolic pathways, increases in intracellular calcium and the activation of endoplasmic reticulum stress. These processes adversely affect β-cells by impairing insulin secretion, decreasing insulin gene expression and ultimately causing apoptosis. In this review, we will first discuss the regulation of β-cell mass during normal conditions. Then, we will discuss the mechanisms of β-cell failure, including glucotoxicity, lipotoxicity and endoplasmic reticulum stress. Further research into mechanisms will reveal the key modulators of β-cell failure and thus identify possible novel therapeutic targets.